Triple Curve Scoliosis Presented with Developmental Dysplasia of the Left Hip in Marfan Syndrome - Lukas Widhiyanto; Tri Wahyu Martanto; Febrian Brahmana (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2018)
Introduction: Marfan syndrome is an autosomal dominant disorder of connective tissue, and skeletal system involvements are the cardinal features.  Triple rigid large major curve in conjunction with developmental dysplasia of the hip in Marfan syndrome is rare then sagittal and coronal imbalance correction on this case is challengingCase Presentation: We reported a case of 12 years old female with Marfan syndrome presented triple rigid large Major curve scoliosis on left cervico-thoracal, right main  thoracal and left thorakolumbal, also developmental dysplasia of the left hip has been done correction surgery consist of open reduction following cast immobilization of the left hip, multiple ponte osteotomy and asymetrical pedicle substraction osteotomy to correct sagittal and coronal imbalance.Discussion: the treatment of scoliosis in patients with Marfan syndrome parallels that in patients with idiopathic scoliosis and spinal fusion and instrumentation should be considered for curves greater than 45 to 50 degrees. Posterior technique, Ponte osteotomy correct 10 to 20 degrees and pedicle substraction osteotomy correct 30 to 40 degrees at each segment are effective for managing sagittal and coronal imbalance in scoliosis. Open reduction developmental dysplasia of the hip to overcome complicated coronal balance correction.Conclusion : Detailed planning scoliosis surgery is needed to correct a rare the sagittal and coronal imbalance due to scoliosis complicated with developmental dysplasia of the hip in Marfan syndrome.